2008
DOI: 10.1021/ja806930h
|View full text |Cite
|
Sign up to set email alerts
|

Silica Sodalite without Occluded Organic Matters by Topotactic Conversion of Lamellar Precursor

Abstract: Novel pure silica sodalite with hollow sodalite-cages has been synthesized for the first time by topotactic conversion of layered silicate (RUB-15) precursor. This success has been achieved by stepwise syntheses from silicate monomers, through clusters and layers, to microporous crystals. The pretreatment of layered silicate with small carboxylic acids before conversion is a crucial step. The obtained sodalite possesses accessible micropores, as confirmed by physical adsorption of hydrogen molecules. This plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 19 publications
0
73
0
Order By: Relevance
“…The indirect layered precursor routes were subsequently identified for some traditional zeolites, well-known for years via minerals and synthetic solids, i.e., ferrierite [16] and sodalite [17]. A hypothesis was formulated [15] that many, if not most, zeolite structures may be accessible by both direct and indirect pathways, currently represented only by the 2-D layered precursors but in general one cannot rule out others, such as 1-D species (A reviewer kindly pointed out that Akporiaye and Price [4] and Shannon [5] had already demonstrated that most zeolites could be built by the stacking of layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indirect layered precursor routes were subsequently identified for some traditional zeolites, well-known for years via minerals and synthetic solids, i.e., ferrierite [16] and sodalite [17]. A hypothesis was formulated [15] that many, if not most, zeolite structures may be accessible by both direct and indirect pathways, currently represented only by the 2-D layered precursors but in general one cannot rule out others, such as 1-D species (A reviewer kindly pointed out that Akporiaye and Price [4] and Shannon [5] had already demonstrated that most zeolites could be built by the stacking of layers.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrierite and some newer precursors showed additional complexity [16,17,[25][26][27][28][29] associated with silanol distribution on the surface of the layers, which in turn relates to internal symmetry of these layers.…”
Section: Layered Precursors With Fer Sheetsmentioning
confidence: 99%
“…Syntheses were performed under hydrothermal conditions at 150°C for 3 weeks in Teflon lined autoclaves. The typical gel composition is: SiO 2 :0.5SDA:xH 2 O where x = 8-12 [1]. The concentration of the trivalent T-atom was in the range of 1-5% in terms of molar ratio of SiO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The thermal post-synthesis treatment of hydrous layer silicates has proven to be a successful method to obtain 3-dimensional zeolitic materials not only with unique and unexpected morphologies [2], but also with new framework topologies. However, because of the all-silica compositions of the layered precursors, the new zeolite frameworks as condensation products were primarily obtained in their all silica form [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Another related material, called EU-20b, formed from calcining its precursor, EU-19 prepared with a piperazinium SDA, was found to form an intergrowth material composed of NSI and CAS framework layers [151]. Acetic acid treatment was found to decrease the distance between the layers of RUB-15 from 14 to 7.7Å, allowing the conversion of the material to the pure-silica SOD framework upon calcination [152]. The key to the success of the acetic acid treatment was that it allowed the layers to shift one half unit cell along the c-axis to align the layers, which does not occur by treatment with hydrochloric acid.…”
Section: Layered Precursorsmentioning
confidence: 99%